Abinukitrine A, a unique 17, 18-cyclolanostane triterpenoid from Abies nukiangensis. Issue 8 (5th February 2019) - Li, Yong-Li; Xue, Li-Jun; Li, Jie; Chen, Li-Ming; Wu, Jian-Jun; Xu, Zhuo-Ni; Chen, Ying; Tian, Yu-Ping; Yang, Xian-Wen
Abstract : Abinukitrine A was isolated from Abies nukiangensis as the first example of 17, 18-cyclolanostane. It showed a potent anti-hepatitis C virus effect. Abstract : Abinukitrine A (1 ), a novel triterpenoid, was isolated from Abies nukiangensis . Comprehensive spectroscopic analysis revealed that1 is the first example of 17, 18-cyclolanostane bearing a unique 6/6/6/5/3 ring system. Its absolute configuration was unequivocally assigned by Cu-Kα X-ray single-crystallography. Compound1 showed a potent anti-hepatitis C virus (HCV) effect.